Interferon gamma inhibits CXCL8–CXCR2 axis mediated tumor-associated macrophages tumor trafficking and enhances anti-PD1 efficacy in pancreatic cancer - Mingjie Zhang; Lifeng Huang; Guoping Ding; Huilian Huang; Guoliang Cao; Xu Sun; Neng Lou; Qiang Wei; Tao Shen; Xiaodong Xu; Liping Cao; Qiang Yan (Journal for ImmunoTherapy of Cancer)
Background Pancreatic cancer (PC) is a common malignancy of the digestive system and is characterized by poor prognosis and early metastasis. Tumor immune escape plays an important role in PC progression. Programmed death 1 (PD1) blockade therapy is a promising treatment for patients with PC, but is yet to achieve significant clinical effects so far. Interferon gamma (IFN-γ) is a soluble dimeric cytokine that is closely associated with tumor immune surveillance and cytotoxicity. IFN-γ suppresses a variety of tumor-derived cytokines in PC, such as CXCL8. In the present study, we investigated the therapeutic efficacy of combined anti-PD1 and IFN-γ treatment in PC.Methods BxPC-3 and Panc-1 human PC cell lines were used to construct a murine PC model. Blood samples (n=44) and surgical resection specimens (n=36) from human patients with PC were also collected. χ2 test, two-tailed unpaired t-test or Kaplan-Meier survival analysis was used to calculate p values.Results PD1/PD-L1 signaling was overexpressed in PC tumor-bearing mice. Anti-PD1 prevented tumor growth if initiated early after tumor inoculation; however, delayed anti-PD1 treatment showed limited benefit. Murine PC model had a preferential expansion of CXCR2+CD68+ macrophages, and these cells showed an immunosuppressive nature (M2 polarization). PC tumors overexpressed CXCL8 and tumor-derived CXCL8 deficiency prohibited the trafficking of CXCR2+CD68+ macrophages. IFN-γ suppressed the expression of tumor-derived CXCL8, and combined with IFN-γ treatment, delayed anti-PD1 treatment showed significant antitumor effects. Thus, we conclude that murine CXCR2+CD68+ macrophages traffic to PC tumors by tumor-derived CXCL8 and mediate local immunosuppression, which limits the efficacy of PD1 blockade therapy. IFN-γ suppresses tumor-derived CXCL8 and inhibits the tumor trafficking of CXCR2+CD68+ macrophages by blocking the CXCL8–CXCR2 axis to enhance anti-PD1 efficacy. Human PC also produces high levels of CXCL8. Patients with PC present elevated CXCR2 expression on peripheral and tumor-infiltrating CD68+ macrophages, which are associated with advanced tumor stage and poor prognosis.Conclusion Our findings suggest that IFN-γ is a translatable, therapeutic option to improve the efficacy of PD1 blockade therapy by preventing trafficking of CXCR2+CD68+ macrophages via blocking the CXCL8–CXCR2 axis.